Intelligent Routing in Mobile Opportunistic Networks - Kosmides, Pavlos; Lambrinos, Lambros (My University, 2018)
Over the last couple of decades, mobile devices have evolved in many ways with powerful processing and high storage capabilities being complemented by a number of sensors and communication interfaces. Exploiting their wireless communication capabilities, mobile devices form intermittently connected networks, known as Mobile Opportunistic Networks. In such networks, devices exchange data packets opportunistically. Dynamic topology changes and difficulty in the routing process often result in long delays with user location data along with social characteristics being potentially useful in the process. In this paper, we propose the deployment of an intelligent network controller, based on the principles of software-defined networks that will collect and process context data from the available wireless networks, users, and social networks. We describe the architecture of our system, analyse component interactions and present the business processes and related application services. We demonstrate the experimental results from a use case scenario for estimating the contact duration between opportunistically connected mobile nodes.
Keywords: Intelligent Routing; Machine Learning; Mobile Opportunistic Networks; Software Defined Networks